Varisela Neonatal - Lina Purnamasari (PT Kalbe Farma Tbk., 2023)
Varicella or chickenpox is a highly contagious infectious disease. Transmission of varicella-zoster infections in neonates can occur through transplacental (congenital), or postnatal (acquired) route. Diagnosis of neonatal varicella is based on contact history and clinical presentation. Neonatal varicella had risk for severe disease and high mortality rate.